Exploring the Effect of Shocking Advertising Used by For-Profit and Nonprofit Organizations in the US and China - Yan, Shuo; Chapa, Sindy (Journal of Marketing Development and Competitiveness, 2020)
The purpose of this study is to explore the effectiveness of shocking advertising when applied by a nonprofit versus a for-profit organization. Particularly, this study aims to evaluate the effectiveness of shocking ads in terms of attitude toward the ad (Aad), brand attitude (Ab), and intention to behave by comparing consumers’ cognitive responses to shocking and non-shocking ads. A total sample of 343 was collected in China and the US. Overall, the results indicate consumers held more positive Aad and Ab toward non-shocking ads than toward shocking ads. When both using shocking advertising, consumer elicited more positive Ab and intention to behave toward the nonprofit organization than the for-profit organization. Chinese and American consumers held more negative Aad toward shocking than non-shocking ads. Moreover, consumers’ Ab toward the shocking/for-profit organization are similarly low in both countries, suggesting both Chinese and American consumers dislike the shocking ad as well as the sponsored for-profit organization. Lastly, similarly high intention to behave was elicited toward nonprofit organizations regardless the form of ads.